LIPID PROFILE CHANGES IN WISTAR RATS EXPOSED TO METHYLATED SPIRIT AND CARBONATED COLA: IMPLICATIONS FOR YOUTH SUBSTANCE ABUSE IN NIGERIA - Ofori , Chika Elizabeth; Nwosu, Samuel Chukwuemeka (Research Journal of Health, Medicine and Nursing, 2024)
This study is an attempt to provide primary data on how some of these novel mixtures impact the body. It aims to determine the effects of a mixture of methylated spirit and a carbonated cola drink on the lipid profile of male wistar rats as a means of assessing its health impact. Male wistar rats were obtained from the animal house of the Department of Biochemistry, University of Benin, Edo state, Nigeria. Methylated spirit and carbonated cola drinks were purchased from Otuoke Pharmacy, Otuoke, Bayelsa state and used for the research. Methylated spirit (50ml) was added to 50ml of cola drink in a beaker to obtain 100ml of the mixture. The animals were grouped into 3: A, B and C with seven animals in each group. A single dose of 0.1ml of the mixture were orally administered to those in group A and 0.2ml to those in group B using plastic oral intubation and gavage tube. Those in group C where orally administered 1 ml of distilled water and served as the control. The concentrations of total cholesterol, high density lipoprotein, low density lipoprotein, triglyceride and very low density lipoprotein were analyzed using semi-automated biochemistry analyzer with standard reagent kits. The result of the investigation reveals that intake of the mixture increased the mean levels of total cholesterol (3.774± 0.82????????????????/ ????), triglyceride (2.026± 0.42????????????????/????), high density lipoprotein (1.468± 0.25????????????????/????), low density lipoprotein (1.385± 0.38????????????????/????), very low density lipoprotein (0.9205± 0.19????????????????/????) for group A and total cholesterol (2.782± 0.03????????????????/ ????), triglyceride (1.450± 0.68????????????????/????), high density lipoprotein (1.043± 0.17????????????????/????), low density lipoprotein (1.080± 0.16????????????????/????), very low density lipoprotein (0.659± 0.31????????????????/ ????) for group B when compared to the control total cholesterol (4.671± 0.13????????????????/ ????), triglyceride (0.6160± 0.10????????????????/????), high density lipoprotein (1.084± 0.01????????????????/????), low density lipoprotein (3.321± 0.05????????????????/????), very low density lipoprotein (0.2910± 0.03????????????????/????). The observed altered the lipid profiles in the experimental subjects may initiate further metabolic changes as high lipid levels have been associated with weight gain, obesity and atherosclerosis. Although alcohol is a substance of complex physiological effects that vary according to gender, age, race, body weight and consumption patterns, methanol as used in the mixture is not advisable, because its continual consumption will result in the development of cardiovascular diseases in abusers